Reduction of air microbism in the operating room through ozone: experiences carried out in the Prof. Eduardo Blanco Acevedo Clinic’s - García Capurro, Rafael; Lucas Gafre, A (Cirugía del Uruguay, 2020)
Presented at session 3rd July 1940